Teaching Traditions of Introduction to Social Sciences and Characteristics of Methods for Introducing Social Sciences to Early Childhood - Musafir, Musafir; Mulianah, Maedatul; Muliati, Muliati; Wahidah, Wiratul; Wulandari, Neti (Jurnal Ilmiah Mandala Education (JIME), 2025)
Teaching social sciences to early childhood has an important role in shaping their understanding of society, culture and social interactions. This article discusses the tradition of introducing social sciences and the characteristics of the methods used in teaching young children. By using a qualitative approach and data analysis from various sources, this research aims to provide a clear picture of how social studies teaching can be carried out effectively and relevantly. The results of the analysis show that various methods, such as project-based learning and role-playing, can increase children's involvement and understanding of social concepts.